USE OF THE SIX SIGMA METHOD TO REDUCE BAD CONE DEFECTS AND IMPROVE QUALITY IN THE SPINNING UNIT OF PT. DAN LIRIS - Diah Ayu Purwitasari; Yunita Primasanti; Erna Indriastiningsih (Jurnal Disprotek, 2026)
The textile industry must produce high-quality products with low defect rates to improve competitiveness and customer satisfaction. This research was conducted at the spinning unit of PT. Dan Liris, which still faces problems with bad cone defects in the winding process, such as wrinkles, crossing, ring cones, dirty yarn, and weights that do not meet standards. This study aims to analyse the level of bad cone defects, identify the main causal factors, and provide improvement suggestions to improve yarn product quality. The method used Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, and Control) approach. Data were obtained from the production results of winding machines from July 2024 to March 2025. The analytical tools used include Pareto diagrams, P control charts, fishbone diagrams, and Failure Mode and Effect Analysis (FMEA) to determine improvement priorities based on the Risk Priority Number (RPN) value. The results show that the dominant defects are wrinkles and crossing, with DPMO values and initial sigma levels indicating that the process still needs improvement. The factors causing defects come from aspects of machines, work methods, materials, and people. Kaizen-based improvement proposals reduced the number of bad cone defects, decreased the DPMO value, and increased the process sigma level. Thus, the implementation of the Six Sigma method has proven effective in improving yarn product quality and supporting zero-defect efforts at the spinning unit of PT. Dan Liris.PENGGUNAAN METODE SIX SIGMA UNTUK MENGURANGI CACAT BAD CONE DAN MENINGKATKAN KUALITAS PADA UNIT SPINNING PT. DAN LIRISIndustri tekstil dituntut untuk menghasilkan produk dengan kualitas tinggi dan tingkat kecacatan yang rendah guna meningkatkan daya saing dan kepuasan pelanggan. Penelitian ini dilakukan pada unit spinning PT. Dan Liris yang masih menghadapi permasalahan cacat bad cone pada proses winding, seperti wrinkle, crossing, ring cone, benang kotor, serta berat tidak sesuai standar. Penelitian ini bertujuan untuk menganalisis tingkat kecacatan bad cone, mengidentifikasi faktor penyebab utama, serta memberikan usulan perbaikan guna meningkatkan kualitas produk benang. Metode yang digunakan adalah Six Sigma dengan pendekatan DMAIC (Define, Measure, Analyze, Improve, dan Control). Data diperoleh dari hasil produksi mesin winding periode Juli 2024 hingga Maret 2025. Alat analisis yang digunakan meliputi diagram Pareto, peta kendali P, diagram fishbone, serta Failure Mode and Effect Analysis (FMEA) untuk menentukan prioritas perbaikan berdasarkan nilai Risk Priority Number (RPN). Hasil penelitian menunjukkan bahwa cacat dominan adalah wrinkle dan crossing, dengan nilai DPMO dan level sigma awal yang menunjukkan proses masih perlu ditingkatkan. Faktor penyebab cacat berasal dari aspek mesin, metode kerja, material, dan manusia. Usulan perbaikan berbasis Kaizen mampu menurunkan jumlah cacat bad cone, menurunkan nilai DPMO, serta meningkatkan level sigma proses. Dengan demikian, penerapan metode Six Sigma terbukti efektif dalam meningkatkan kualitas produk benang dan mendukung upaya zero defect di unit spinning PT. Dan Liris.